Simulated Sound-Fields in a Multi-Configurable Auditorium - BUSTAMANTE, Pedro; GIRÓN, Sara; ZAMARREÑO, Teófilo (Archives of Acoustics, 2014)
In this work, simulation techniques have been implemented to study the sound fields of a multi-configurable performance enclosure by creating computer acoustic 3D-models for each room configuration. The digital models have been tuned by means of an iterative fitting procedure that uses the reverberation times measured on site for unoccupied conditions with the orchestra shell on the stage. The initial virtual acoustic model is validated by comparing the other monaural and binaural acoustic parameters measured in the room in terms of their perception differential threshold. The procedure is applied to The Maestranza Theatre of Seville, built for the Universal Exhibition in 1992. The spatial distribution of the acoustic parameters in the audience area of the venue by measured parameters and simulation mappings enables the establishment of three zones of acoustic comfort, which are corroborated by the values of the Ando-Beranek function which provide a global quality coefficient of each zone.